JAK2 V617F mutation in plasma cell-free DNA preceding clinically overt myelofibrosis: Implications for early diagnosis. Issue 8 (3rd August 2018) - Choi, Michael Y.; Kato, Shumei; Wang, Huan-You; Lin, Jonathan H.; Lanman, Richard B.; Kurzrock, Razelle
ABSTRACT: A 52 year-old man with Erdheim-Chester Disease (ECD) (a non-Langerhans polyostotic sclerosing histiocytosis) had next-generation sequencing (NGS) performed as part of his diagnostic workup. In addition to the tissue BRAF V600E mutation that is found in over 50% of ECD cases, he was also found to have a JAK2 V617F alteration in cell-free circulating tumor DNA (ctDNA) (liquid biopsy). The latter was thought to be an "incidental" finding, perhaps due to clonal hematopoiesis (though this usually occurs in older individuals), as his blood counts were normal and he had no splenomegaly. Approximately 13 months after the ctDNA test showing JAK2 V617F, he developed anemia, thrombocytopenia, and splenomegaly. Marrow biopsy then showed megakaryocytic atypia and markedly increased marrow fibrosis, consistent with WHO grade 2 of 3 myelofibrosis. Therefore, the patient was determined to have ECD with a typical BRAF V600E mutation, as well as primary myelofibrosis, with the latter diagnosis manifesting clinically over one year after the JAK2 V617F was first detected in ctDNA. He recently was started on the JAK2 inhibitor ruxolitinib. This case demonstrates that genomic alterations detected by liquid biopsy for evaluation of specific malignancies already present may serve as an early harbinger of hematological disease.